An Unusual Relationship : Evangelical Christians and Jews - Ariʼel, Yaʻaḳov (Book collections on Project MUSE., 2013)
This volume offers a fascinating, comprehensive analysis of the roots, manifestations, and consequences of evangelical Christians' interest in the Jews.